2018
DOI: 10.1038/s41370-018-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin exposure in children living in Mirpur, Dhaka: data from MAL-ED companion study

Abstract: Dietary exposure to aflatoxin is implicated in growth faltering of children. Despite the high burden of childhood stunting in urban Bangladesh, there are no data on long-term exposure to aflatoxin. This study aimed to explore aflatoxin exposure levels in a group of children followed longitudinally. The current study used data and biospecimens collected during 2010-2014 as part of the MAL-ED birth cohort study in an urban slum of Mirpur, Dhaka where children were followed from birth to 36 months. AFB1-lysine ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
(55 reference statements)
3
20
1
Order By: Relevance
“…These results, discussed by the authors in the context of biomarker data for cohorts in other countries, document rather high AFB 1 exposures of their cohort in the Northwest of Bangladesh between 2008 and 2012. A recent longitudinal study in an urban slum in Dhaka city assessed AFB 1 exposure of children at the age of 7, 15, 24 and 36 months and reported a geometric mean of 1.07 pg AFB 1 -Lys/mg albumin and a range of 0.04–123.5 pg AFB1-Lys/mg albumin (Mahfuz et al 2019 ). In this study, a reduction in breastfeeding prevalence, with concomitant introduction of family food, corresponded with an increase in AFB 1 -lysin adduct detection at 36 months, and 62% of the children were exposed at the end of their 3 rd year of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, discussed by the authors in the context of biomarker data for cohorts in other countries, document rather high AFB 1 exposures of their cohort in the Northwest of Bangladesh between 2008 and 2012. A recent longitudinal study in an urban slum in Dhaka city assessed AFB 1 exposure of children at the age of 7, 15, 24 and 36 months and reported a geometric mean of 1.07 pg AFB 1 -Lys/mg albumin and a range of 0.04–123.5 pg AFB1-Lys/mg albumin (Mahfuz et al 2019 ). In this study, a reduction in breastfeeding prevalence, with concomitant introduction of family food, corresponded with an increase in AFB 1 -lysin adduct detection at 36 months, and 62% of the children were exposed at the end of their 3 rd year of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known so far about mycotoxin exposure in Bangladeshi children: two studies investigated AFB 1 exposure in young children, one in a rural site in the North of the country, the other in an urban slum in Dhaka (Groopman et al 2014 ; Mahfuz et al 2019 ). Both have analyzed AFB 1 -lysin albumin in blood, a biomarker which integrates exposure during the course of several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…To release AFB1-lysine (AFB1-lys) adduct from albumin, proteins in serum samples are digested with Pronase ® for a few hours at 37 • C. AFB1-lys is then extracted and purified with SPE by means of a mixed-mode anion exchange reversed-phase matrix. Next, the analytes are eluted, mainly through the use of methanol (MeOH) with formic acid, then concentrated and reconstituted in the mobile phase before analysis with LC-MS/MS [49,65,81,83,87,[112][113][114][115], LC-FLD [81,[88][89][90][91][92] or ELISA [73][74][75][76][77][78][79]117]. McCoy et al (2008) [70] and Scholl et al (2006) [123] reported good correlations of the concentration levels obtained from ELISA, LC-FLD and LC-MS.…”
Section: Mycotoxin Biomarkers In Human Blood Plasma and Serummentioning
confidence: 99%
“…A number of studies have been carried out to evaluate the presence of AFs in plasma or serum from children with severe acute malnutrition (SAM) in Kenya [92], Nigeria [49], Tanzania [113,117] Uganda [88,90], Mexico [81,91] and other countries [75,[77][78][79]83,87,114,115]. This is a particularly relevant topic due to the rates of childhood growth disorders in these countries.…”
Section: Mycotoxin Biomarkers In Human Blood Plasma and Serummentioning
confidence: 99%
See 1 more Smart Citation